Visible Spectrophotometric Determination of Famciclovir in Bulk and Pharmaceutical Dosage Formulations - NIZAMUDDIN, SYED; GOLI, DIVAKAR; MANOHARA, Y.N.; RAVI, M.C. (Asian Journal of Chemistry, 2010)
Two simple colorimetric methods for the estimation of famciclovir in pharmaceutical dosage forms. In method A famciclovir undergoes complexation with SNP and to form coloured chromogen exhibiting absorption maximum at 428 nm and obeyed Beer's law in the concentration range of 2-12 μg/mL. In the method B based on the formation of an ion pair with bromocresol green in acidic medium and the subsequent extraction of the ion pair in chloroform. The yellow coloured ion pair showed an absorption maximum at 421 nm with apparent molar absorptivity. The proposed methods gave reproducible results for the estimation of famciclovir from its pharmaceutical formulation.